The Relationship between Serum Level of Vitamin D and Depression Severity with Sexual Function in a Sample of Iranian Women in the Year 2017 - Fatemeh Jalali-Chimeh; Tayebeh Darooneh; Giti Ozgoli; Maliheh Nasiri; Mohammadreza Vafa (مجله دانشکده پزشکی اصفهان, 2017)
Background: Few available studies suggest the possible role of vitamin D deficiency in sexual dysfunction. The relationship between vitamin D deficiency and depression is still considered challenging issue. According to the bilateral relationship between depression and sexual dysfunction, this study aimed to determine the relationship of serum level of vitamin D and depression severity with sexual function in a sample of Iranian women with sexual dysfunction in the year 2017.